Consideration of sense of coherence in a structured communication approach with stage IV lung cancer patients and their informal caregivers: a qualitative interview study - Krug, Katja; Bossert, Jasmin; Stooß, Lydia; Siegle, Anja; Villalobos Bollen, Matthias Americo; Hagelskamp, Laura; Jung, Corinna; Thomas, Michael; Wensing, Michel (Supportive care in cancer, 2021)
Salutogenetic aspects are valuable for consideration in patient-centred care of advanced oncological diseases with a limited life expectancy. The Milestone Communication Approach (MCA), involving physician-nurse tandems, addresses specific challenges and needs over the disease trajectory of patients with stage IV lung cancer and their informal caregivers. This study aims to explore patients’ and informal caregivers’ salutogenetic experiences with the MCA concept.
Published online: 3 September 2020
Gesehen am 04.10.2021